Implantable devices in the electromagnetic environment. Issue 6 (30th July 2013) - Santini, Luca; Forleo, Giovanni B.; Santini, Massimo
Abstract: In the last few years we are witnessing a dramatic increase in the number of CIEDs implanted. At the same time new emitters are constantly entering the marketplace and more and more medical procedures are based on electromagnetic fields as well. Therefore, the topic of the interaction of CIEDs with the EMI is a real, actual and challenging one. In the non‐medical environment several types of devices may be intentional or non‐intentional sources of EMI. Most of the studies reported in literature focused on mobile phones, metal detectors, as well as on headphones or digital players, but many other instruments and tools may generate electromagnetic fields. In the medical environment most of the attention is paid to MRI and recently new PM and MRI conditional ICDs have been developed and launched in the market, but the risk of interaction is present also with ionizing radiation, electrical nerve stimulation and electrosurgery. Pacemaker/ICD manufacturers are incorporating state of the art technology to make implantable devices less susceptible to EMI. However, patients and emitter manufacturers should be aware that limitations exist and that there is not complete immunity to EMI.